Impact of COVID-19 on the lives of vulnerable young people in New Delhi, India: a mixed method study - Shanti Raman; Rajeev Seth; Sharanya Napier-Raman; Ananya Rattani; Yawar Qaiyum; Vijayluxmi Bose (BMJ Publishing Group, 2021)
Background India is home to the largest child population in the world. India also has faced a devastating burden of COVID-19 infections. During the first wave of COVID-19, the Indian government's lockdown measures brought loss of livelihoods for millions. We aimed to explore the social, psychological and health impacts of the government's pandemic measures on children and young people (CYP), and their families.Methods Bal Umang Drishya Sanstha (BUDS) is a non-profit organisation providing child health and welfare services to marginalised urban slum communities in New Delhi, India. As part of formative evaluation of BUDS's COVID-19 pandemic relief efforts, the team conducted a rapid survey of 60 children (10-17 years) and 62 young adults (18-25 years) who were beneficiaries of the relief programme. The team also undertook semi-structured interviews with nine young women attending BUDS's second-chance education programme.Results Almost all respondents had some understanding of COVID-19 (54 children (90%) and 53 young adults (85%)) and the reasons for public health measures (59 children (98%) and 56 young adults (90%)). Over 80% of girls and 60% of boys experienced financial strains and food shortages. Gender discrepancies were particularly evident in areas of family stress, with girls and young women disproportionately experiencing distress and family violence. Girls were more likely to be fearful of contracting the disease, while boys were more concerned about getting back to school. In-depth interviews with young women revealed that government ration schemes were insufficient to support vulnerable families; there were interesting cultural understandings of and responses to the pandemic. Young women reported high rates of anxiety and distress.Conclusions The lockdown had a multitude of adverse social, health and psychosocial effects on marginalised CYP, disproportionately affecting girls and young women. A tailored response based on equity and child rights is urgently required to address concerns voiced by CYP.